An introduction to 'other effective area‐based conservation measures' under Aichi Target 11 of the Convention on Biological Diversity: Origin, interpretation and emerging ocean issues. (September 2017) - Laffoley, Dan; Dudley, Nigel; Jonas, Harry; MacKinnon, David; MacKinnon, Kathy; Hockings, Marc; Woodley, Stephen
Abstract: The new term 'other effective area‐based conservation measures', or OECMs, was introduced into Aichi Biodiversity Target 11 of the Convention on Biological Diversity's (CBD) Strategic Plan by signatory Parties in 2010. In the intervening period much action has been taken on creating protected areas as the key route to delivering area‐based conservation of biodiversity and ecosystem services. Rather less attention has been paid to OECMs due in part to a lack of guidance on what areas should or should not be included under this label. An IUCN World Conservation Congress Resolution in 2012 called on IUCN's World Commission on Protected Areas (WCPA) to assist the CBD by providing technical guidance on interpretation of the wording in Aichi Biodiversity Target 11. IUCN WCPA established a Task Force in 2015 to provide guidance on OECMs, in terrestrial, freshwater and marine habitats. This Task Force has already met several times and has a global membership of more than 100 experts. The official call made by the CBD in 2016 for guidance explicitly recognizes the role of the IUCN Task Force in fulfilling this guidance need. This paper provides the background to OECMs and an initial analysis on the type and nature of measures that may qualify as OECMs under Aichi Target 11. Successful implementation will be dependent on clear principles and guidance, but also on a far better awareness among conservationists and other sectors on the purpose and scope of all 20 Aichi Targets. The paper will also be of value to discussions and implementation of Sustainable Development Goal 14 on the ocean. Some generic examples of areas likely to qualify as OECMs in the ocean are identified, along with an analysis of how OECMs complement and supplement fisheries and other management measures to promote more sustainable use. Greater recognition and reporting is needed on fisheries measures under Aichi Target 6. All fishery management and exclusion zones will not qualify as OECMs, but they can form essential measures towards achieving delivery of greater sustainability within such extractive industries.